Decoding metabolic connections: the role of salivary amylase activity in modulating visceral fat and triglyceride glucose index - Gita Erta; Gita Gersone; Antra Jurka; Peteris Tretjakovs (Lipids in Health and Disease)
Abstract Background Salivary amylase activity (SAA) is recognized as a potential biomarker for metabolic health. Previous studies suggest an association between SAA and insulin sensitivity, but the mechanisms remain unclear. This study investigates the relationship between SAA, visceral fat (VF), and the triglyceride-glucose (TyG) index to clarify the pathways linking SAA to metabolic risk factors. Methods This cross-sectional study analysed data from women of reproductive age who were classified as overweight. Linear regression models were used to assess associations between salivary amylase activity (SAA), visceral fat (VF) and the triglyceride-glucose (TyG) index, while adjusting for confounding variables such as age, body mass index (BMI), physical activity and dietary patterns. Mediation analysis was conducted to determine whether VF mediates the relationship between SAA and the TyG index. Results Higher SAA was inversely associated with VF (β = -0.45, 95% CI: -0.65 to -0.25, p < 0.001). No direct association was observed between SAA and TyG index (β = -0.10, 95% CI: -0.25 to 0.05, p = 0.18) after adjustment for covariates. Mediation analysis revealed that visceral fat significantly mediated the relationship between SAA and the TyG index. The indirect effect of SAA on the TyG index through VF (A × B) was statistically significant (β = -0.16, 95% CI: -0.26 to -0.08), accounting for 45% of the total effect. Conclusions These findings suggest that higher SAA may confer metabolic benefits by reducing VF, thereby indirectly influencing the TyG index. This highlights the critical role of VF in mediating the protective effects of SAA on metabolic health and provides insights into potential pathways for intervention.